Math, asked by Anonymous, 14 days ago

Question: Find dx/dy if x = a(cosθ+θsinθ), and y = a(sinθ−θsinθ).​

Answers

Answered by rabbitkimjisoo7
4

Answer:

I found this i hope this will help you

Attachments:
Answered by mathdude500
4

\large\underline{\sf{Solution-}}

Given that

\rm \: x = a(cos\theta  + \theta sin\theta ) \\

On differentiating both sides w. r. t.  \theta , we get

\rm \: \dfrac{d}{d\theta }x = a\dfrac{d}{d\theta }(cos\theta  + \theta sin\theta ) \\

\rm \: \dfrac{dx}{d\theta } = a\bigg(\dfrac{d}{d\theta }cos\theta  + \dfrac{d}{d\theta }\theta sin\theta\bigg ) \\

\rm \: \dfrac{dx}{d\theta } = a\bigg( - sin\theta  + \theta \dfrac{d}{d\theta } sin\theta + sin\theta \dfrac{d}{d\theta }\theta \bigg ) \\

\rm \: \dfrac{dx}{d\theta } = a\bigg( - sin\theta  + \theta cos\theta + sin\theta  \times 1 \bigg ) \\

\rm \: \dfrac{dx}{d\theta } = a\bigg( - sin\theta  + \theta cos\theta + sin\theta   \bigg ) \\

\bf\implies \:\dfrac{dx}{d\theta } = a \: \theta  \: cos\theta  -  -  - (1) \\  \\

Further given that

\rm \: y = a(sin\theta  - \theta sin\theta ) \\

can be rewritten as

\rm \: y = asin\theta(1  - \theta) \\

On differentiating both sides w. r. t.  \theta , we get

\rm \:\dfrac{d}{d\theta } y = a\dfrac{d}{d\theta }sin\theta(1  - \theta) \\

\rm \:\dfrac{dy}{d\theta } = a\bigg(sin\theta \dfrac{d}{d\theta }(1  - \theta)  + (1 - \theta )\dfrac{d}{d\theta }sin\theta \bigg)\\

\rm \:\dfrac{dy}{d\theta } = a\bigg(sin\theta (0 - 1)  + (1 - \theta )cos\theta  \bigg)\\

\rm \:\dfrac{dy}{d\theta } = a\bigg( - sin\theta  + (1 - \theta )cos\theta  \bigg)\\

\bf\implies \:\dfrac{dy}{d\theta } = a\bigg( - sin\theta  + cos\theta  - \theta cos\theta  \bigg)\\  \\

Now,

\rm \: \dfrac{dx}{dy} \\

\rm \:  =  \: \dfrac{dx}{d\theta } \div \dfrac{dy}{d\theta } \\

\rm \:  =  \: \dfrac{a \: \theta  \: cos\theta }{a( - sin\theta  + cos\theta  - \theta cos\theta) }  \\  \\

\rm \:  =  \: \dfrac{\theta  \: cos\theta }{ - sin\theta  + cos\theta  - \theta cos\theta}  \\

Hence,

 \\ \bf\implies \:\dfrac{dx}{dy}   =  \: \dfrac{\theta  \: cos\theta }{ - sin\theta  + cos\theta  - \theta cos\theta}  \\  \\

\rule{190pt}{2pt}

Formulae Used :-

\boxed{ \rm{ \:\dfrac{d}{dx}x = 1 \: }} \\

\boxed{ \rm{ \:\dfrac{d}{dx}sinx = cosx\: }} \\

\boxed{ \rm{ \:\dfrac{d}{dx}cosx =  -  \: sinx\: }} \\

\boxed{ \rm{ \:\dfrac{d}{dx}uv \:  =  \: u\dfrac{d}{dx}v \:  +  \: v\dfrac{d}{dx}u \: }} \\

Similar questions